Burial Practices and its Making Reasons in Mesopotamia During Sumerian era ( the third Millennium B.C ) - Shahood, Ahmad; Al Hawash, Tammam (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research sheds light on the most important Ceremonies and Practices of the dead's burying which had been done during the ancient Mesopotamian civilization, These beliefs had a special importance in the religious beliefs and the social traditions of the ancient Mesopotamians Civilization, Starting from their belief that death is determinism result on all human beings, and the immortality is a trait which gods only have and Soul deprives from moving to the dead's world and stabilizing in it if the body of its owner is deprived from burying or making the burial practices and giving the Sacraments for him. From this principle, Sumerians had made their burial practices on the deads for the dead's souls have a favour of comfort in the dead's world, from here the interest of this study came during a specific period